Livestock, food chain and public health risk assessment - Smeu, Irina (EFSA J, 2019)
The EUropean FOod Risk Assessment (EU‐FORA) Fellowship work programme ‘Livestock, food chain and public health risk assessment’, founded by EFSA was proposed by the Animal and Plant Health Agency (APHA), United Kingdom (UK). A scientist working in the field of food safety was selected to work within the Department of Epidemiological Sciences, under the guidance of an experienced risk assessor. The programme was structured in four different modules that covered a wide range of aspects related to risk assessment (RA). Taken together, all modules ensured a broad overview of the various methodologies, tools and applications of RA. Thus, the learning‐by‐doing working programme in RA allowed the fellow to develop her knowledge in RA, to diversify her competencies and to extend her scientific network for future collaborations in the field of RA.